High resolution analysis of the FTIR spectra of trifluoroamine NF3; Journal of Molecular Spectroscopy; Vol. 348 - Bolotova I. B. Irina Batorovna; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Albert S. Sieghard; Hollenstein H. A. Hans; Quack M. Martin; Peter T.; Seyfang G. Georg; Wokaun A. Alexander (2018, 2018)
Title screen